An independently controlled energy storage to support short term frequency fluctuations in weak electrical grids - Jayamaha, Prasanthi Charmalee; Costabeber, Alessando; Williams, Arthur; Sumner, M. (Elsevier, 2018)
This paper proposes the use of Energy Storage (ES) to support frequency fluctuations in weak grids powered by low-power synchronous generators (SGs). Traditionally, large synchronous generators rely on high inertia and governor control to guarantee the frequency stability of the network. The scenario changes in networks with a large penetration of small distributed generators (DGs) with smaller inertia, where load variations can lead to large frequency deviations, violating the over/under frequency protection limits. The proposed energy storage control injects active power during load transients so that the frequency is constrained within predefined thresholds. The system frequency is detected by a Double Second-Order Generalised Integrator Frequency Locked Loop (DSOGI-FLL), eliminating the need for communication between energy storage and synchronous generator and providing “plug-and-play” capability. The proposed method combined with the continuous speed governing supports the frequency well within the primary frequency transient requirements. The solution has been validated using an 8kW laboratory system.